Global Oral Health Policies and Guidelines: Using Silver Diamine Fluoride for Caries Control - Gao, Sherry Shiqian; Amarquaye, Gwendolyn; Arrow, Peter; Bansal, Kalpana; Bedi, Raman; Campus, Guglielmo; Chen, Kitty Jieyi; Chibinski, Ana Cláudia Rodrigues; Chinzorig, Tselmuun; Crystal, Yasmi O.; Duangthip, Duangporn; Ferri, María Laura; et al. (Frontiers in Oral Health, 2021)
Silver diamine fluoride (SDF) was developed in Japan in the 1960s. It is a clear solution containing silver and fluoride ions. Because of its anti-bacterial and remineralizing effect, SDF has been used in managing dental caries for decades worldwide. The paper aims to summarize and discuss the global policies, guidelines, and relevant information on utilizing SDF for caries management. SDF can be used for treating dental caries in most countries. However, it is not permitted to be used in mainland China. Several manufacturers, mainly in Australia, Brazil, India, Japan, and the United States, produce SDF at different concentrations that are commercially available around the world. The prices differ between contents and brands. Different government organizations and dental associations have developed guidelines for clinical use of SDF. Dental professionals can refer to the specific guidelines in their own countries or territories. Training for using SDF is part of undergraduate and/or postgraduate curriculums in almost all countries. However, dentists’ real utilization of SDF, especially in the private sector, remains unclear in most places because little research has been conducted. There are at least two ongoing regional-wide large-scale oral health programs using SDF as one of the components to manage dental caries in young children (one in Hong Kong and one in Mongolia). Because SDF treatment does not require caries removal, and it is simple, non-invasive and inexpensive, SDF is a valuable strategy for caries management in young children, elderly people and patients with special needs. In addition, to reduce the risk of bacteria or virus transmission in dental settings, using SDF as a non-aerosol producing procedure should be emphasised under the COVID-19 outbreak.